The Prevalence of Hypomagnesemia in Critically Ill Patients Admitted in Medically Intensive Care Unit - Maryam Farhan Baloch; Azeem Khalid; Kiran Naimat; Muhammad Usman Khalid; Muhammad Abdul Khaliq Khan; Shahzaib Maqbool (University Library System, University of Pittsburgh, 2023)
Background Magnesium is the fourth most abundant cation in the human body. Hypomagnesemia can result from decreased intake, redistribution of magnesium from the extracellular to the intracellular space, or increased renal or gastrointestinal loss. Hypomagnesemia can cause severe outcomes in ill patients. So, we conducted this study to determine the frequency of hypomagnesemia in critically ill medical patients. Methods This is a Descriptive cross-sectional study involving 120 patients admitted in the medical intensive care unit (MICU) of the Holy Family Hospital, Rawalpindi, Pakistan. The study was conducted from July 2020 to September 2021. About 1 ml sample of blood was taken from each patient included and sent to the hospital laboratory for evaluation of serum magnesium levels. All the collected data was entered and analyzed on SPSS v. 23. A p-value of ≤ 0.05 was taken significant. Results In our study, the mean age of the patients was 42.76±12.77 years, and the male-to-female ratio of the patients was 1:1. The mean value of the APACHE II score of the patients was 29.68±2.571. Hypomagnesemia was found in 28 (23.33%) patients. Conclusion According to our study, the frequency of hypomagnesemia in critically ill medical patients was 23.33% (28 patients).